Antifungal, toxicological, and colorimetric properties of Origanum vulgare, Moringa oleifera, and Cinnamomum verum essential oils mixture against Egyptian Prince Yusuf Palace deteriorative fungi - Asmaa Alhussein Mohamed; Mahgoub A. Ahmed; Abdallah S. Korayem; Samah H. Abu-Hussien; Wael Bakry Rashidy (BMC Biotechnology)
Abstract The increasing demand for sustainable alternatives to conventional antifungal agents has prompted extensive research into the antifungal properties of plant essential oils (EOs). This study investigates the use of EOs mixture (Origanum vulgare, Moringa oleifera, and Cinnamomum verum) for controlling fungal deterioration in wall paintings at the archaeological Youssef Kamal Palace in Nag Hammadi, Egypt. Fungal isolates were collected from deteriorated wall paintings and identified using phenotypic and genotypic analyses. Aspergillus sp. was found to be the predominant species (50%), followed by Penicillium sp. (16.7%), Fusarium sp. (16.7%), and others. They were genetically identified to be Aspergillus oryzae, Aspergillus niger, Penicillium chrysogenum, Fusarium solani, Alternaria alternata, Botrytis cinerea, and Trichoderma viride. The antifungal activity of three individual oils (oregano, moringa and cinnamon) was evaluated against the most predominant A. niger strain. Out of the three oils, oregano oil showed the strongest antifungal effect with an inhibition zone diameter (IZD) of 4.5 cm followed by moringa (3.5 cm) and cinnamon (3.2 cm). A mixture design approach optimized the EOs combination, with the most effective composition being (44% oregano, 46% moringa, 10% cinnamon), yielding an IZD of 6.5 cm. The optimized EOs mixture demonstrated complete inhibition against all tested fungal strains. The minimal inhibitory concentration tests showed varying efficacies against different fungal strains, with MIC values ranging from 125 to 500 µg/mL. GC-MS analysis identified the major bioactive compounds: carvacrol (83.25%) in oregano, trans-13-octadecenoic acid (22.62%) in moringa, and cinnamaldehyde (24.42%) in cinnamon. Cytotoxicity testing on human skin fibroblasts (HSF) showed minimal toxicity of EOs mixture with 87.64% cell viability at 100 µg/ml. Colorimetric measurements revealed some colour changes in experimental painting samples, particularly with cinnamon oil on white pigment (ΔE = 9.64) and moringa oil on a yellow pigment (ΔE = 16.31). However, oregano oil consistently showed the least impact across all pigments. These findings demonstrate the potential of the EOs combination as an effective, eco-friendly approach to mitigating fungal deterioration in wall paintings, contributing to sustainable conservation strategies for cultural heritage preservation.